The Gut-Brain Axis in Neurodegenerative Diseases and Relevance of the Canine Model: A Review - Ambrosini, Yoko M.; Borcherding, Dana; Kanthasamy, Anumantha; Kim, Hyun Jung; Willette, Auriel A.; Jergens, Albert; Allenspach, Karin; Mochel, Jonathan P. (Frontiers in Aging Neuroscience, 2019)
Identifying appropriate animal models is critical in developing translatable in vitro and in vivo systems for therapeutic drug development and investigating disease pathophysiology. These animal models should have direct biological and translational relevance to the underlying disease they are supposed to mimic. Aging dogs not only naturally develop a cognitive decline in many aspects including learning and memory deficits, but they also exhibit human-like individual variability in the aging process. Neurodegenerative processes that can be observed in both human and canine brains include the progressive accumulation of β-amyloid (Aβ) found as diffuse plaques in the prefrontal cortex (PFC), including the gyrus proreus (i.e., medial orbital PFC), as well as the hippocampus and the cerebral vasculature. Tau pathology, a marker of neurodegeneration and dementia progression, was also found in canine hippocampal synapses. Various epidemiological data show that human patients with neurodegenerative diseases have concurrent intestinal lesions, and histopathological changes in the gastrointestinal (GI) tract occurs decades before neurodegenerative changes. Gut microbiome alterations have also been reported in many neurodegenerative diseases including Alzheimer’s and Parkinson’s diseases, as well as inflammatory central nervous system (CNS) diseases. Interestingly, the dog gut microbiome more closely resembles human gut microbiome in composition and functional overlap compared to rodent models. This article reviews the physiology of the gut-brain axis (GBA), and its involvement with neurodegenerative diseases in humans. Additionally, we outline the advantages and weaknesses of current in vitro and in vivo models and discuss future research directions investigating major human neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases using dogs.